2017
DOI: 10.1111/jir.12436
|View full text |Cite
|
Sign up to set email alerts
|

Rate and characteristics of urgent hospitalisation in persons with profound intellectual disabilities compared with general population

Abstract: In contrast to previous results reported for the group with ID as a whole, patients with PID consulting the emergency service were not admitted to hospital more frequently than the general population nor did they present a higher rate of inappropriate admissions. These results support the utility of maintaining two distinct groups of people with ID: mild-moderate and severe-profound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The only study identified by the authors to report no difference in ACS admission rates between people with profound ID and those without ID was that of Amor‐Salamanca and Menchon from Barcelona, Spain (Amor‐Salamanca and Menchon ). These authors however were reporting the rate of admission of individuals who attended hospital emergency departments, not people in the population.…”
Section: Introductionmentioning
confidence: 99%
“…The only study identified by the authors to report no difference in ACS admission rates between people with profound ID and those without ID was that of Amor‐Salamanca and Menchon from Barcelona, Spain (Amor‐Salamanca and Menchon ). These authors however were reporting the rate of admission of individuals who attended hospital emergency departments, not people in the population.…”
Section: Introductionmentioning
confidence: 99%
“… Predictors of Emergency Room and Hospital Utilization Among Adults with Intellectual and Developmental Disabilities 23 Blaskowitz, M. G.; Hernandez, B.; Scott, P. W. 2019 USA Adults with intellectual and developmental disability n: 597 None Age, gender, level of intellectual disability, chronic health problems, mental health diagnoses, polypharmacy, supported living arrangement, region ER use for a medical/physical reason, hospitalization for a medical/physical reason, ER use for a behavioral/psychiatric reason, hospitalization for a behavioral/psychiatric reason Prevalence study, secondary data: survey of medical charts Predictors (environmental and individual risk factors) for ED use: institutionalized people are less likely to be admitted; people from deprived neighborhoods with a lack of care are less likely to visit the ED 2. Rate and characteristics of urgent hospitalization in persons with profound intellectual disabilities compared with general population 24 Amor-Salamanca, A.; Menchon, J. M. 2018 Spain Adults with severe/ profound intellectual disability n: 28 Other hospitalized ED patients n: 83 Gender, age, living arrangement Emergency visits, admission to hospital after emergency visit Retrospective cohort study, secondary data: discharge reports No differences in the proportion of people with profound intellectual disability and controls admitted to hospital after their emergency visit; the median hospital stay was higher for people with profound intellectual disability s: 7.5 vs 4 days for controls 3. Factors associated with ambulatory care sensitive emergency department visits for South Carolina Medicaid members with intellectual disability 25 McDermott, S.; Royer, J.…”
Section: Methodsmentioning
confidence: 99%
“… Emergency Department Use: Common Presenting Issues and Continuity of Care for Individuals with and without Intellectual and Developmental Disabilities 34 Durbin, A.; Balogh, R.; Lin, E.; Wilton, A. S.; Lunsky, Y. 24 2018 Canada Adults with intellectual and developmental disability n: 66,484 Adults without intellectual and developmental disability n: 2,760,670 Level of continuity of primary care ED visits Retrospective cohort study, secondary data: administrative health and social services data Individuals with intellectual and developmental disability were more likely than individuals with no intellectual and developmental disability to visit the ED; for both groups, greater primary care continuity was associated with less ED use, but this relationship was more marked for adults with intellectual and developmental disability 13. Use of health services in the last year of life and cause of death in people with intellectual disability: a retrospective matched cohort study 35 Brameld, K.; Spilsbury, K.; Rosenwax, L.; Leonard, H.; Semmens, J.…”
Section: Methodsmentioning
confidence: 99%
“…Intellectually disabled (ID) patients present unique therapeutic challenges. They demand more medical resources than the general population [1] and have higher rates of hospital and intensive care unit (ICU) admission [2].…”
Section: Introductionmentioning
confidence: 99%
“…ID patients suffer lifelong disability and early mortality [4,5]. Compared to the general population, they undergo more hospitalizations [2] and when hospitalized have longer lengths of in-hospital stay [4,6]. They are admitted more frequently after surgical procedures, have more complications [7,8] and are also more likely to die during hospitalization [9,10].…”
Section: Introductionmentioning
confidence: 99%